Anatomía de la zona distal de los dedos medios del pie - Viejo Tirado, Fermín; Prados Frutos, Juan Carlos (Revista Internacional de Ciencias Podológicas, 2007)
In this revision, the authors try to illustrate the referring to the descriptive anatomy of the distal area of the lesser toes of the foot. It contains, a description detailed from the embryonic development of these sections, the osteology of the phalanges, joints and basic mechanics of them, tendons, blood vessels, lymphatic, and nervous system. All these anatomical parts are described with illustrations and extracted pictures of preserved and fresh foot specimens.